Subjective socioeconomic status is associated with risk aversion in a community-based cohort of older adults without dementia - Weissberger, Gali H.; Han, S. Duke; Yu, Lei; Barnes, Lisa L.; Lamar, Melissa; Bennett, David A.; Boyle, Patricia A. (Frontiers in Psychology, 2022)
Attitudes towards risk impact financial decisions that are critical in older adulthood. Socioeconomic status (SES) influences an individual’s level of risk aversion; however, the association of subjective SES (i.e., social standing relative to others) with risk aversion has not been explored. We examined whether subjective SES is associated with risk aversion independent of objective SES (i.e., income, education). Participants were 933 older adults without dementia from the Rush Memory and Aging Project (MAP) or Minority Aging Research Study (MARS), two longitudinal epidemiologic studies of aging. Participants completed assessments of risk aversion, subjective SES, and cognition. We examined associations of subjective SES with risk aversion using mixed models adjusting for participant characteristics, objective markers of SES and global cognition. In bivariate analyses, lower global cognitive functioning, lower income, female sex, Black race, and lower subjective SES were associated with greater risk aversion. Results of the nonlinear mixed effects model revealed that higher subjective SES was associated with less risk aversion (Estimate = -0.238, SE = 0.083, p = 0.004), after controlling for covariates. Age, sex, race, and global cognition were also associated with risk aversion in the mixed effects model (ps ≤ 0.03), although income and education were not (ps ≥0.27). The relationship between subjective SES and risk aversion did not differ by sex or race (ps ≥.31). Findings suggest that subjective SES contributes to risk aversion regardless of sex or race. Findings support the importance of considering subjective indicators of SES as they may impact an older adult’s economic preferences.